Understanding the use of kaikaku project management in construction industry: A planned behaviour approach - Lee, Chia Kuang; Chung, Jacquelene Aie Nie; Muhammad Ashraf, Fauzi (Construction Research Institute of Malaysia, 2024)
The project management method used in every project plays a vital role in determining the success of a project. Kaikaku Project Management (KPM) is beneficial in many ways, however, the implementation of the method in the construction industry in Malaysia is not common. To address the issue above, the aim of this study is to (1) identify the relationship between attitude, subjective norm, perceived behavioural control towards the use of Kaikaku project management, 2) elicit behavioural, normative and control beliefs with regards to the use of Kaikaku project management, 3) examine the influence between behavioural, normative and control beliefs towards attitude, subjective norms and perceived behavioural control. This study uses the mixed-methods approach in which Belief Elicitation Study (BES) is used to identify salient beliefs that is thematically analysed and reclassified into nine constructs to form the Theory of Planned Behaviour (TPB) survey. Nineteen (19) professionals from the construction industry took part in the Belief Elicitation Study (BES) while ninety-five (95) contractors from G5, G6 and G7 took part in the Theory of Planned Behaviour (TPB) survey. The PLS-SEM analysed data showed that the professional institute, government and client have no significant effect on the subjective norms towards KPM and the perceived behavioural control (PBC) has no significant effect toward the intention to use KPM. The perceived usefulness, perceived ease of use, project management team, self-efficacy and facilitating conditions are significant factors towards attitude towards KPM, subjective norms with regards to KPM and perceived behavioural control in KPM. The attitude towards KPM and subjective norms with regards to KPM are significant factors that affects the intention to use KPM.